2015
DOI: 10.1176/appi.neuropsych.13120359
|View full text |Cite
|
Sign up to set email alerts
|

Group Dialectical-Behavior Therapy Skills Training for Conversion Disorder With Seizures

Abstract: Neuroimaging evidence suggests deficits in affective regulation in conversion disorder (CD). Dialectical-behavior therapy skills training (DBT-ST) was developed to target emotion dysregulation. This study was aimed to test the feasibility of stand-alone DBT-ST for CD using Linehan's manual for borderline personality disorder. In a prospective naturalistic design, 19 adult outpatients diagnosed with video EEG-confirmed seizure type CD were recruited and received weekly group DBT. Seventeen out of 19 subjects fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…69 The long-term benefits of therapy and other treatments can be examined in randomized, controlled, clinical trials along with other potential pharmacologic and psychotherapy treatment interventions. 70,71 Outcome and predictor of outcome studies have been performed in PNES. Given that the initial stages of treatment include accurate diagnosis and effective communication of the diagnosis, it is noteworthy that diagnostic acceptance by patients improves outcomes.…”
Section: Treatment and Outcome Studiesmentioning
confidence: 99%
“…69 The long-term benefits of therapy and other treatments can be examined in randomized, controlled, clinical trials along with other potential pharmacologic and psychotherapy treatment interventions. 70,71 Outcome and predictor of outcome studies have been performed in PNES. Given that the initial stages of treatment include accurate diagnosis and effective communication of the diagnosis, it is noteworthy that diagnostic acceptance by patients improves outcomes.…”
Section: Treatment and Outcome Studiesmentioning
confidence: 99%
“…DBT distinguishes itself from ACT in that it provides both a conceptual framework as well as a focus on relevant skill acquisition (e.g., emotion regulation skills) that maps onto an emotion dysregulation conceptualization of conversion disorder. Indeed, a small pilot study with individuals diagnosed with conversion disorder with seizures demonstrated preliminary feasibility and effectiveness of a group-based DBT approach that focused on distress tolerance, emotion regulation, and interpersonal effectiveness, with decreases in mean seizure rates of 66% and complete remission of seizures in 35% of participants (Bullock, Mirza, Forte, & Trockel, 2015).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…Similar to the approach used by Bullock and colleagues (2015), treatment loosely followed the path of teaching distress tolerance skills, followed by emotion regulation and interpersonal effectiveness. These mapped on to the skill deficits identified related to Jane’s primary treatment targets (i.e., suicidal ideation, alcohol use, interpersonal effectiveness).…”
Section: Course Of Treatment and Assessment Of Progressmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) DBT skills use has been shown to mediate the decreases in suicide attempts, non-suicidal self-injury, depression and anger in individuals with BPD. (10) There have been emerging trials demonstrating the clinical utility of DBT skills training alone (DBT-ST) in patients with depressive disorders (11,12); substance use disorders (13,14); attention de cit hyperactivity disorder (ADHD) (15,16) and conversion disorder with seizures (17). Emotion dysregulation is a common feature across multiple diagnostic categories, and DBT-ST appears to be a promising treatment for depressed and anxious transdiagnostic adults.…”
Section: Introductionmentioning
confidence: 99%